Advances in sickle cell disease treatments - Pavan, Aline Renata [UNESP]; Dos Santos, Jean Leandro [UNESP] (Bentham Science Publishers, 2021)
Sickle Cell Disease (SCD) is an inherited disorder of red blood cells that is caused by a single mutation in the β-globin gene. The disease, which afflicts millions of patients worldwide mainly in low income countries, is characterized by high morbidity, mortality and low life expectancy. The new pharmacological and non-pharmacological strategies for SCD is urgent in order to promote treatments able to reduce patient’s suffering and improve their quality of life. Since the FDA approval of HU in 1998, there have been few advances in dis-covering new drugs; however, in the last three years voxelotor, crizanlizumab, and glutamine have been approved as new therapeutic alternatives. In addition, new promising compounds have been described to treat the main SCD symptoms. Herein, focusing on drug discovery, we discuss new strategies to treat SCD that have been carried out in the last ten years to discover new, safe, and effective treatments. Moreover, non-pharmacological approaches, including red blood cell exchange, gene therapy and hematopoietic stem cell transplantation will be pre-sented.
Keywords: Antisickling; Fetal hemoglobin; Iron chelation; New drugs; Nitric oxide; Red blood cell; Sickle cell disease